Factors causing timely referral for fetal echocardiography in the final diagnosis of congenital heart malformations: A cross-sectional study - Mojgan Barati; Nahal Nasehi; Sareh Aberoumand; Mahin Najafian; Abdolrahman Emami Moghadam (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Congenital heart disease (CHD) is one of the most frequently inherited illnesses associated with adverse outcomes. Objective: This study aimed to determine the referral cause for fetal echocardiography in the final diagnosis of major CHD. Materials and Methods: In this cross-sectional study, the data of 1772 pregnant women, referred to a diagnostic clinic during 2017-2020, were reviewed. Data were collected from participants on maternal age, gestational age, history of previous child's heart disease, body mass, the order of birth of children (baby birth rank), type of woman's disease, history of poor midwifery, and nuchal translucency (NT). Results: Of the 1772 pregnant women, only 33 women (1.8%) had a fetus with CHD major. Abnormality in ultrasound (57.6%), history of abortion (36.4%), increased NT and gestational diabetes (18.2%) and gestational diabetes (18.2%) were identified as the most common referral reasons for fetal echocardiography in these women. Other reasons included a previous child with Down syndrome (12.1%), a previous child with heart disease (12.1%), a history of stillbirth (12.1%), hypothyroidism (12.1%), taking medication during the pregnancy period (9.0%), no underlying disease (9.0%), multiple pregnancies (6.0%), diagnosis with high-risk fetal heart disease (3.0%), high-risk combined aneuploidy screening test in the first trimester (3.0%), in vitro fertilizationpregnancy (3.0%), and having a child with an intellectual disability (3.0%). Conclusion: According to the results, it can be concluded that ultrasound abnormality, abortion, increased NT and gestational diabetes are the most important factors for referring pregnant women for fetal echocardiography.